That ain't witchcraft - McGuire, Seanan (McGuire, Seanan. InCryptid novel., 2019)
Antimony Price has never done well without a support system. As the youngest of her generation, she has always been able to depend on her parents, siblings, and cousins to help her out when she<U+2019>s in a pinch<U+2014>until now. After fleeing from the Covenant of St. George, she<U+2019>s found herself in debt to the crossroads and running for her life. No family. No mice. No way out. Lucky for her, she<U+2019>s always been resourceful, and she<U+2019>s been gathering allies as she travels: Sam, fūri trapeze artist turned boyfriend; Cylia, jink roller derby captain and designated driver; Fern, sylph friend, confidant, and maker of breakfasts; even Mary, ghost babysitter to the Price family. Annie<U+2019>s actually starting to feel like they might be able to figure things out<U+2014>which is probably why things start going wrong again. New Gravesend, Maine is a nice place to raise a family<U+2026>or make a binding contract with the crossroads. For James Smith, whose best friend disappeared when she tried to do precisely that, it<U+2019>s also an excellent place to plot revenge. Now the crossroads want him dead and they want Annie to do the dirty deed. She owes them, after all. And that<U+2019>s before Leonard Cunningham, aka, “the next leader of the Covenant,” shows up<U+2026> It<U+2019>s going to take everything Annie has and a little bit more to get out of this one. If she succeeds, she gets to go home. If she fails, she becomes one more cautionary tale about the dangers of bargaining with the crossroads.